Microbial community profiles in soils adjacent to mining and smelting areas: Contrasting potentially toxic metals and co-occurrence patterns. (November 2021) - Liu, Bang; Yao, Jun; Ma, Bo; Chen, Zhihui; Zhao, Chenchen; Zhu, Xiaozhe; Li, Miaomiao; Cao, Ying; Pang, Wancheng; Li, Hao; Feng, Lingyun; Mihucz, Victor G.; et al.
Abstract: Mining and smelting activities have introduced severe potentially toxic metals (PTMs) contamination into surrounding soil settings. Influences of PTMs on microbial diversity have been widely studied. However, variations of microbial communities, network structures and community functions in different levels of PTMs contaminated soils adjacent to mining and smelting aera are still poorly investigated. In this study, microbial communities of soils around different levels of PTMs contamination were comprehensively studied by 16S rRNA gene amplicons high-throughput sequencing. Microbial interactions and module functions were also exploited to ascertain the discrepancies of PTMs concentration levels on microbial ecological functions. Results indicated that the microbial community composition was significantly distinct attributed to the phylum Protebacteria ( p = 0.002) dominating in soil with high level PTMs contents but Actinobacteria ( p = 0.002) in low level of PTMs-contaminated soil. Microbial α diversity was not significantly influenced by different levels of PTMs contaminations. Microorganisms proactively responded to PTMs content levels by means of strengthening network complexities and modularities among microbe-microbe interactions. The functions of main network modules were predicted associating membrane transport, amino acid metabolism, energy metabolism and carbohydrate metabolism. The PTMs detoxification and anti-oxidation were significantly strengthened at the high level of PTMs contamination. The present study demonstrated that modification of microbial community by the adaptive adjustment of microbial compositions and strengthening their network complexity and modularity. Graphical abstract: Image 1 Highlights: Microbial α diveristy was not significantly influenced by metals levels. Proteobacteria and Acidobacteria contributed to the varations of microbiota. Potentially toxic metals increased network complexities. Functions of main network modules were predicted. Bio-detoxification and anti-oxidation were key pathway against PTMs stress.